2015
DOI: 10.1071/mf15159
|View full text |Cite
|
Sign up to set email alerts
|

Sydney Harbour: what we do and do not know about a highly diverse estuary

Abstract: Sydney Harbour is a global hotspot for marine and estuarine diversity. Despite its social, economic and biological value, the available knowledge has not previously been reviewed or synthesised. We systematically reviewed the published literature and consulted experts to establish our current understanding of the Harbour’s natural systems, identify knowledge gaps, and compare Sydney Harbour to other major estuaries worldwide. Of the 110 studies in our review, 81 focussed on ecology or biology, six on the chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 124 publications
0
38
0
Order By: Relevance
“…Our study area, Sydney Harbour, is a modified system, where centuries of human development interact with a diverse rocky shoreline. The state government of New South Wales have regularly mapped key habitats in coastal estuaries including Sydney Harbour from aerial imagery (Creese, Glasby, West, & Gallen, ), but community scale (<5–10 m) data are lacking (Hedge et al., ; Johnston et al., ; Mayer‐Pinto, Underwood, & Marzinelli, ; Mayer‐Pinto, Johnston et al., ). Sydney Harbour has worldwide recognition as an iconic and biologically diverse estuary, but has typically been the subject of studies dissecting the effects of contaminants, invasive species, and artificial structures on marine ecology (Johnston et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study area, Sydney Harbour, is a modified system, where centuries of human development interact with a diverse rocky shoreline. The state government of New South Wales have regularly mapped key habitats in coastal estuaries including Sydney Harbour from aerial imagery (Creese, Glasby, West, & Gallen, ), but community scale (<5–10 m) data are lacking (Hedge et al., ; Johnston et al., ; Mayer‐Pinto, Underwood, & Marzinelli, ; Mayer‐Pinto, Johnston et al., ). Sydney Harbour has worldwide recognition as an iconic and biologically diverse estuary, but has typically been the subject of studies dissecting the effects of contaminants, invasive species, and artificial structures on marine ecology (Johnston et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…The state government of New South Wales have regularly mapped key habitats in coastal estuaries including Sydney Harbour from aerial imagery (Creese, Glasby, West, & Gallen, ), but community scale (<5–10 m) data are lacking (Hedge et al., ; Johnston et al., ; Mayer‐Pinto, Underwood, & Marzinelli, ; Mayer‐Pinto, Johnston et al., ). Sydney Harbour has worldwide recognition as an iconic and biologically diverse estuary, but has typically been the subject of studies dissecting the effects of contaminants, invasive species, and artificial structures on marine ecology (Johnston et al., ). Remnant inundated and semi‐inundated habitats in Sydney Harbour include a variety of rocky reef habitats, seagrasses, soft sediments, saltmarshes, and mangroves, while more than half of the natural shoreline has been converted to hard artificial structures (Mayer‐Pinto, Johnston et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of the loggers used in this study were deployed close to marine/tide dominated estuaries (e.g., Jervis Bay) with low and intermittent freshwater inflows (and thus shallow intermittent river plumes, e.g., Johnston et al, 2015). This is in agreement with Stobart et al (2016), who also found that the proximity to estuaries did not explain differences between in situ and satellite data in the vicinity of FIGURE 10 | Mean temperature differences between in situ and satellite that was processed at each logger location using an area average of 8 km across shelf and 20 km along shelf with a rolling mean based on the de-correlation time for the in situ location to fill in missing data (i.e.…”
Section: Satellite-derived Temperaturesmentioning
confidence: 99%